-6y+3(-4y+5)=-9-4(-2-y)

Simple and best practice solution for -6y+3(-4y+5)=-9-4(-2-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y+3(-4y+5)=-9-4(-2-y) equation:



-6y+3(-4y+5)=-9-4(-2-y)
We move all terms to the left:
-6y+3(-4y+5)-(-9-4(-2-y))=0
We add all the numbers together, and all the variables
-6y+3(-4y+5)-(-9-4(-1y-2))=0
We multiply parentheses
-6y-12y-(-9-4(-1y-2))+15=0
We calculate terms in parentheses: -(-9-4(-1y-2)), so:
-9-4(-1y-2)
determiningTheFunctionDomain -4(-1y-2)-9
We multiply parentheses
4y+8-9
We add all the numbers together, and all the variables
4y-1
Back to the equation:
-(4y-1)
We add all the numbers together, and all the variables
-18y-(4y-1)+15=0
We get rid of parentheses
-18y-4y+1+15=0
We add all the numbers together, and all the variables
-22y+16=0
We move all terms containing y to the left, all other terms to the right
-22y=-16
y=-16/-22
y=8/11

See similar equations:

| 4p-3=9p+13 | | 4.8(x-3.75)=19.2 | | -5x=-4x-5 | | 5(1+1x)=20 | | 2(n-1)=-4n+28 | | 2(5b+3)-4=2/3(12b+8) | | 6m-3=-15 | | 6+6v+2-v=5v+8 | | 12x•2=12.5+15 | | 32+8n=-8+2n | | 4(1+2x)=6x-10 | | -80=-16p | | 5x+2=-7x+3 | | 12h-8h+2=10 | | -5a+6=-2(4a+15) | | -160=8(-6x+4) | | Y+x+75=180 | | -2(x-8)+6=22-2x | | c+581=936 | | 12+2x=-5(x-8) | | 5x+4x+18=3x+3 | | 4x-(2x-1)=x+(5)+x-(6) | | 5v=-3v+16 | | -19c=-836 | | -4(2-6x)=-30+2x | | –11d–5=17 | | -11=m-1+4m | | 6+6x=3+6x | | -(12x+-6)=12x+6 | | 6(w-4)+8w=2(w+12) | | -48=6a | | 4x+11=1+2x |

Equations solver categories